Work Overload dan Turnover: Pengaruh Mediasi Job Satisfaction Pada Restoran di Kawasan Wisata Ubud - Cokorda Istri Agung Vera Nindia Putri; I Wayan Meryawan; Tjokorda Gde Agung Wijaya Kesuma Suryawan; Ni Kadek Sintya Agustini (Widya Manajemen, 2026)
The growing number of restaurants and the increase in tourist visits to Bali have had a significant impact on the economy of the restaurant industry, but it is not in line with the willingness of employees to work sustainably in restaurants. Indications of high work overload and declining job satisfaction are the causes of employee insecurity. Greenkubu Restorant and Swing faces a high number of employees continuing to increase from 2022-2024. This study seeks to understand job satisfaction in mediating the relationship between work overload and employee turnover intention of Greenkubu Restaurant and Swing. Quantitative approach using SEM-PLS analysis using questionnaires distributed to all restaurant employees as a source of hypothesis test data, the study revealed that work overload had a positive and significant effect on turnover intention. On the other hand, workoverload has a significant negative effect on job satisfaction and job satisfaction has a significant negative effect on turnover. Meanwhile, job satisfaction partially mediates the relationship between work overload and turnover intention. These results provide guidance for tourism restaurant managers to suppress the high desire of employees to leave work through efforts to manage employee workoverload which has an impact on job satisfaction and can ultimately reduce high turnover rates.